Playing the harmonica with chronic obstructive pulmonary disease. A qualitative study. (7th March 2022) - Lewis, Adam; Conway, Joy; Middleton, Jack; Startup, Chris K; Wyatt, James
Objectives: To investigate the experience of playing the harmonica for individuals with COPD. Methods: A qualitative, phenomenological study using semi-structured interviews and reflexive thematic analysis. Results: Eight people living with COPD (six females, two males) were recruited, who had attended at least six weeks of harmonica group sessions, either face-to-face prior to the COVID-19 pandemic or remotely. Five themes were generated. Themes included 'hard in the beginning', 'holding the condition', 'breathing control', 'gives you a high' and 'needing the Zoom class'. Discussion: Playing the harmonica with COPD is difficult at first, particularly drawing a breath through the harmonica. With practice, experience in a fun activity and quality teaching, individuals were able to become more attuned and embodied with their breathing, and playing the harmonica offered a breathing control strategy. Songs, rather than breathing, became the focus, and participants were able to escape living with respiratory disease when playing. Participants reported the harmonica helped mucous expectoration. The group was a priority in the weekly lives of participants, even though the 'buzz' of being part of a group was lost when participating online. Further mechanistic studies and randomised controlled trials are needed to investigate the biopsychosocial benefits of playing the harmonica with COPD.